SMART TOURISM TECHNOLOGIES: APPLICATIONS TO THE HOTEL INDUSTRY AND TOURISM - Egamberdiyev , Sirojiddin Sattor o‘g‘li (Innovative Development in Educational Activities, 2023)
In modern times, technology permeates every aspect of human existence and is the single biggest element influencing people’s lifestyles. People are using technology more and more, which has a big impact on how businesses run. As technology advances, new service forms and improved versions of current products and services are created. The potential benefits and downsides of smart tourism are briefly discussed after this. The research that is sorely needed to guide the development and management of smart tourism is further highlighted in this study.